Patient outcomes following surgical management of multinodular goiter: Does multinodularity increase the risk of thyroid malignancy?. Issue 28 (July 2016) - Lin, Yann-Sheng; Wu, Hsin-Yi; Yu, Ming-Chin; Hsu, Chih-Chieh; Chao, Tzu-Chieh
Abstract: Background: the difference in the risk of thyroid malignancy for patients with multinodular goiter (MNG) and solitary nodular goiter (SNG) remains controversial. Although total thyroidectomy (TT) is the current preferred surgical option for MNG, permanent hypothyroidism in these patients may be a concern. Therefore, we discuss whether nontotal thyroidectomy is a reasonable alternative surgical option. Methods: A retrospective cohort study was performed for 1598 consecutive patients who underwent thyroid surgery for nodular goiter between January 2007 and December 2012. Numerous clinical parameters were collected and analyzed. Results: We reviewed 795 patients with MNG and 803 patients with SNG. The prevalence of malignancy on final pathology was significantly higher in the patients with MNG than in the patients with SNG (15.6% vs 10.1%, P = 0.001). However, a multivariate analysis revealed that this difference was insignificant ( P = 0.50). Papillary carcinoma was the predominant type in both groups, but papillary microcarcinoma was more frequently found (41.1%) in the patients with MNG. The only multifocal cancers were of the papillary carcinoma histologic type, and the incidence of multifocal papillary carcinoma was significantly higher in the patients with MNG (23.4% vs 7.4%, P = 0.005). Reoperation was not required for the patients who underwent TT for goiter recurrence or incidental carcinoma. The overall rate of recurrence following nontotal thyroidectomy was 12.2%. Among the patients who underwent reoperation for goiter recurrence, 2 (20.0%) were complicated with permanent hypoparathyroidism. Among the patients who underwent a nontotal bilateral thyroidectomy, an average of 56.5% had permanent hypothyroidism. Conclusions: Multinodularity does not increase the risk of thyroid malignancy. However, patients with MNG who develop papillary carcinoma are at an increased risk of cancer multifocality. If a patient can tolerate lifelong thyroid hormone replacement, TT is the preferred surgical option because it helps avoid reoperation and the associated complications. Nontotal bilateral thyroidectomy does not ensure the preservation of thyroid hormone function.